Statistical Study on the Impact of Computer-use on Child-health in the Arab-community - Rahgad, Nasser M. Al-Subaie; Hiafa, Hamuwd A. Al-Subaie; Dhabia, Turki M. Al-Subaie; Sherifa, Mostafa M. Sabra (Journal of Biotechnology and Biomedical Science, 2023)
United States of America (USA), Australia, and Canada recommending children computer-use should be imperfect. It obligated a strong influence on children’s lives. The problem was for stuck in the computer-use for a long time per day. The goal was to follow child-health in the Arab-community to notice its influence on the child-health. The method was through a arithmetical study by sending Internet questionnaire and receiving the parents' advice. The results were in the 500 parent answers and 14 comments. The first was "You have a child up to 13 years old?"; 83.6%. The second was "Your child used a computer?"; 80.8%. The third was "Your child used the computer for a long time?"; 67.9%. The fourth was "The computer caused a health problem for your child?"; 70.3%. The fifth was "The computer caused your child mental disorder?"; 68.5%. The sixth was "The computer caused your child trouble seeing?"; 77.2%. The seventh was "The computer caused your child trouble sleeping?"; 72.0%. The eighth 8 was "The computer caused your child feeding problem?"; 69.5%. The ninth was "The computer caused your child family relationship problem?", 72.0%. The tenth was "Prevent your child from using the computer to protect his health?"; 79.0%. It was concluded that the extent of the harms of child computer-use from a health and psychological point. They have young and sensitive tissues. The computer-use affected them, child-health. It was recommended the parents instructions will protect children from the computer-use for long periods. That will reduce child-health and psychological problems.
Keywords: Computer-use; Child-health; Internet; questionnaire; Parents.